Arabic stories for language learners : traditional Middle Eastern tales in Arabic and English - Brosh, Hezi; Manṣūr, Luṭfī (Tuttle Publishing, 2013)
Arabic Stories for Language Learner's ;a language learning experience for beginner to intermediate students. The traditional stories of a country are invaluable at providing insight into understanding the culture, history and language of a people. The sixty-six stories found in Arabic Stories for Language Learners present the vocabulary and grammar used everyday in Arabic-speaking countries. Pulled from a wide variety of sources that have been edited and simplified for learning purposes, these stories are presented in parallel Arabic and English, facilitating language learning in the classroom and via self-study. Each story is followed by a series of questions in Arabic and English to test comprehension and encourage discussion. Arabic Stories for Language Learners brings Arab culture to life in a colorful and immediate way. Regardless of whether or not you have a working knowledge of Arabic, this book gives readers a tantalizing introduction to the wisdom and humor of these ancient desert-dwelling peoples. Downloadable audio content in Arabic and English helps students of Arabic improve their pronunciation and inflection, and immerses non-students into the uniquely Arabic storytelling style.